2012
DOI: 10.1016/j.comptc.2011.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Revealing substituent effects on the electronic structure and planarity of Ni-porphyrins

Abstract: Using density functional theory, we have studied the effects on structural and electronic consequences (including HOMO-LUMO energy gaps, vertical ionization potentials (IPv), and vertical electron affinities (EAv)) of the following two factors: (a) meso- and β-substituents acting as inductive donors (CH3), inductive acceptors that are electron-donating through resonance (Br), inductive electron acceptors (CF3), and resonance enabled acceptors (NO2); and (b) complete replacement of pyrrole nitrogens with P-atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 90 publications
(78 reference statements)
2
31
0
Order By: Relevance
“…Substituted metalloporphyrin complexes structure however is dependent on the central ion and their substituent group. It had been showed that substituted Ni(II)-porphyrin complexes exhibit a negatively curved structure (hyperbolic) with nearly perfect D2d symmetry with the amount of curvature that varies according to the substituent group [8]. Hg(II)-porphyrin complexes however exhibit a structure with positive curvature (elliptic) with nearly perfect C4v symmetry.…”
Section: Calculation Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Substituted metalloporphyrin complexes structure however is dependent on the central ion and their substituent group. It had been showed that substituted Ni(II)-porphyrin complexes exhibit a negatively curved structure (hyperbolic) with nearly perfect D2d symmetry with the amount of curvature that varies according to the substituent group [8]. Hg(II)-porphyrin complexes however exhibit a structure with positive curvature (elliptic) with nearly perfect C4v symmetry.…”
Section: Calculation Methods Validationmentioning
confidence: 99%
“…On the other side, porphyrin and its derivatives were also known for their unique photoreactivity [1,2] and narrow band gap for semiconductor applications. Some of porphyrin derivatives in the form of metalloporphyrin complexes has been proven to have the properties of a semiconductor materials such as Pt(II)-porphyrin, Fe(II)-porphyrin, Mg(II)-porphyrin and zinc group-porphyrin complexes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors influence the electronic density distribution within the core of the macrocycle and thus determine its reactivity and stability, as well [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…1 showed the HOMO-LUMO energy gap of metalloporphyrin complexes. The previous study performed by Berbee and Kuznetsov [25] proved that electron donating group will destabilize the orbitals resulting in the decrease of band gap energy and increase of orbitals energy. Table 1 also showed that the band gap energy average increased in the series "HgP-R" -"CdP-R" -"PtP-R".…”
Section: Electronic Structurementioning
confidence: 99%